Distortion Correction for 3D Scan of Trunk Swaying Human Body Segments - Funatomi, Takuya; Iiyama, Masaaki; Kakusho, Koh; Minoh, Michihiko (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2009)
We propose a method for acquiring a 3D shape of human body segments accurately. Using a light stripetriangulation range finder, we can acquire accurate 3D shape of a motionless object in dozens of seconds.If the object moves during the scanning, the acquired shape would be distorted. Naturally, humans moveslightly for making balance while standing even if the subject makes an effort to stay still for avoiding thedistortion in acquired shape. Our method corrects the distortion based on measured subject’s motion duringthe scanning.Experimental results show the accuracy of the proposed method. Trunk swaying degrades the accuracyof the light stripe triangulation from 1mm to 10mm. We can keep the accuracy of as good as 2mm byapplying our method.